Molecular Regulation of the Melatonin Biosynthesis Pathway in Unipolar and Bipolar Depression - Dmitrzak-Weglarz, Monika; Banach, Ewa; Bilska, Karolina; Narozna, Beata; Szczepankiewicz, Aleksandra; Reszka, Edyta; Jablonska, Ewa; Kapelski, Paweł; Skibinska, Maria; Pawlak, Joanna (Frontiers in Pharmacology, 2021)
Melatonin is a neurohormone that maintains the circadian rhythms of the body. By regulating the secretion of other hormones and neurotransmitters, it acts as a pleiotropic modulator that affects, for example, reproductive, immune, cardiovascular, sleep, and wake systems and mood. Thus, synthetic melatonin has become an essential component in the treatment of depressive disorders. Although we know the pathway of melatonin action in the brain, we lack comprehensive cross-sectional studies on the periphery of depressed patients. This study aimed to comprehensively analyze the differences between healthy control subjects (n = 84) and unipolar and bipolar depression patients (n = 94), including an analysis of the melatonin pathway at the level of the genes and serum biomarkers. An innovative approach is a pilot study based on gene expression profiling carried out on clinical and cell culture models using agomelatine and melatonin. We confirmed the melatonin biosynthesis pathway's molecular regulation dysfunctions, with a specific pattern for unipolar and bipolar depression, at the AANAT gene, its polymorphisms (rs8150 and rs3760138), and examined the serum biomarkers (serotonin, AANAT, ASMT, and melatonin). The biological pathway analysis uncovered pathways and genes that were uniquely altered after agomelatine treatment in a clinical model and melatonin treatment in a cell culture model. In both models, we confirmed the immunomodulatory effect of melatonin agents in depression.